2022
DOI: 10.1177/1759720x221113747
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in visual involvement of giant cell arteritis: a multicenter study of 471 patients

Abstract: Background: Visual involvement is the most feared complication of giant cell arteritis (GCA). Information on the efficacy of tocilizumab (TCZ) for this complication is scarce and controversial. Objective: We assessed a wide series of GCA treated with TCZ, to evaluate its role in the prevention of new visual complications and its efficacy when this manifestation was already present before the initiation of TCZ. Design: This is an observational multicenter study of patients with GCA treated with TCZ. Methods: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…This observation should be interpreted in the context of the very small sample size. A multi‐centre study 9 of 471 TCZ‐treated GCA patients in Spain found 81 patients had visual involvement at the time of initiation of TCZ. After mean duration of TCZ therapy of 20 months and mean follow‐up of 25 months, no visual deterioration or new visual symptoms occurred in patients previously visually unaffected or experiencing transient visual loss episodes; however, only 18% of patients with partial visual loss had either partial or total improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This observation should be interpreted in the context of the very small sample size. A multi‐centre study 9 of 471 TCZ‐treated GCA patients in Spain found 81 patients had visual involvement at the time of initiation of TCZ. After mean duration of TCZ therapy of 20 months and mean follow‐up of 25 months, no visual deterioration or new visual symptoms occurred in patients previously visually unaffected or experiencing transient visual loss episodes; however, only 18% of patients with partial visual loss had either partial or total improvement.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most serious and feared complications of GCA is vision loss and the use of accelerated glucocorticoid tapering regimens in combination with tocilizumab has raised theoretical concerns regarding possible visual complications. However, data regarding visual outcomes of patients treated with tocilizumab are reassuring (16,17). The few reported cases of vision loss in tocilizumab-treated patients occurred early in the disease course during induction of therapy rather than during the maintenance treatment phase (16).…”
Section: Clinical and Experimental Rheumatology 2023mentioning
confidence: 99%
“…Teceipt of high-dose intravenous glucocorticoids within 6 weeks was an exclusion criterion in GiACTA, the trial may not be able to fully speak to the efficacy of TCZ in patients with threatened vision; one GiACTA patient who received TCZ QOW developed anterior ischemic optic neuropathy during study follow-up which resolved with additional glucocorticoids [10]. In a retrospective study of 471 GCA patients treated with TCZ (intravenous or subcutaneous), 122 patients (26%) had visual involvement at time of TCZ initiation including 60 patients with permanent vision loss (PVL) and 17 patients with transient vision loss (TVL) [15 ▪ ]. Over a mean 25 months of follow-up, none of the patients without visual involvement at TCZ initiation developed new visual symptoms; furthermore, no patients with TVL had further visual episodes.…”
Section: Efficacy Of Tocilizumabmentioning
confidence: 99%